Magnetoelectricity in multiferroic particulate composites with arbitrary crystallographic orientation - Kuo, Hsin-Yi; Kuo, You-Min (My University, 2012)
This paper studies the magnetoelectricity (ME) of a spherical particulate composite made of piezoelectric and piezomagnetic phases. The effects of crystallographic orientations and the volume fraction of inclusion are investigated by a micromechanical approach. The solutions are in good agreement with predictions by finite element analysis. Based on this micromechanical method, we show that, for the CoFe2O4-LiNbO3 particulate composite, the effective ME voltage coefficient can be enhanced at the optimal orientation as compared to those at normal cut orientation. Further, we observe that the ME coupling is sensitive to the piezoelectric constant e(15). The optimal orientation of the ME voltage coefficient is near that of the piezoelectric constant e(15).